2020
DOI: 10.1002/jmv.26101
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between human papillomavirus infection and histopathological diagnosis of women in Northeast Brazil

Abstract: Cervical carcinoma is the fourth leading cause of death among women worldwide. Epidemiological studies claim that human papillomavirus (HPV) infection is a necessary condition for cervical cancer development. Knowledge of the geographic distribution of HPV is important in guiding the introduction of prophylactic vaccines. This study analyzed the prevalence of HPV infection in cervical samples obtained from women with abnormal cervical histopathological diagnosis in Northeast Brazil. The study included an analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
(74 reference statements)
1
3
0
Order By: Relevance
“…Moreover, the results observed here revealed that, when multiple infections were considered, more than half of the participants (57.8%) were infected with genotypes other than 16 and 18, which are not covered by the vaccine used in Brazil (8). This frequency is remarkably high compared to a similar study performed in Northeast Brazil (Agreste region) in women with abnormal cervical histopathological diagnosis, which found 27% of patients infected with HPV other than 16 and 18 (35). These findings have major implications for local public health policies, especially primary prevention strategies, and corroborate the need to identify the genotypic HPV diversity at the regional level.…”
Section: Discussionsupporting
confidence: 61%
“…Moreover, the results observed here revealed that, when multiple infections were considered, more than half of the participants (57.8%) were infected with genotypes other than 16 and 18, which are not covered by the vaccine used in Brazil (8). This frequency is remarkably high compared to a similar study performed in Northeast Brazil (Agreste region) in women with abnormal cervical histopathological diagnosis, which found 27% of patients infected with HPV other than 16 and 18 (35). These findings have major implications for local public health policies, especially primary prevention strategies, and corroborate the need to identify the genotypic HPV diversity at the regional level.…”
Section: Discussionsupporting
confidence: 61%
“…However, there are reported cases where PCR is negative and histology is positive (Figures 4 and 5 ) [ 70 ]. This may be related to the fact that a limited number of viral strains are considered in the PCR test [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Human Papillomavirus (HPV) plays an important role in cervical cancer. Epidemiological studies claim that human papillomavirus (HPV) infection is a necessary condition for cervical cancer development (40)(41)(42). However, the mechanism of HPV in cervical cancer need to be further studied.…”
Section: Discussionmentioning
confidence: 99%